Empagliflozin Alleviates Hepatic Steatosis by Activating the AMPK-TET2-Autophagy Pathway in vivo and in vitro - Li, Ting; Fang, Ting; Xu, Linxin; Liu, Xiangyang; Li, Xiaoyu; Xue, Mei; Yu, Xiaochen; Sun, Bei; Chen, Liming (Frontiers in Pharmacology, 2021)
Background: Metabolic associated fatty liver disease (MAFLD), characterized by hepatic lipid accumulation and fatty degeneration, is intertwined with obesity and type 2 diabetes mellitus (T2DM). Empagliflozin is a sodium-glucose cotransporter-2 inhibitor that effectively lowers blood glucose, but its effect on MAFLD and associated mechanisms are not fully understood. Methods: Eight-week-old db/db mice, an in vivo model, were administered empagliflozin or saline intragastrically. A hepatocyte steatosis model was established by inducing HL7702 cells with high glucose and palmitic acid and then treated with or without empagliflozin. The autophagy inhibitor (3-methyladenine, 3-MA) and AMP-activated protein kinase (AMPK) activator (AICAR)/inhibitor (Compound C) were used to determine the involvement of AMPK and autophagy in the regulation of lipid accumulation by empagliflozin. Ten-eleven translocation 2 (TET2) knockdown was achieved by siRNA transfection. Hepatic steatosis was evaluated by Oil Red O staining and triglyceride quantification. Immunohistochemistry, immunofluorescence, and western blot were performed to assess protein levels. Results: Empagliflozin alleviated liver steatosis in db/db mice and reduced triglyceride content and lipid accumulation in the hepatocyte steatosis model. Empagliflozin elevated autophagy, accompanied by an increase in p-AMPK and TET2. Both 3-MA and Compound C abolished the ability of empagliflozin to induce autophagy and reduce hepatic steatosis, while these effects could be recapitulated by AICAR treatment. TET2 knockdown resulted in autophagy inhibition and lipid accumulation despite empagliflozin treatment. Conclusion and Implications: Empagliflozin improves hepatic steatosis through the AMPK-TET2-autophagy pathway. The use of empagliflozin as a treatment for preventing and treating MAFLD in patients with T2DM warrants further study.